Validity and Reliability of the Brief Version of the RED-Technostress Scale (Revista de Psicología, 2025)
The aim of this work was to generate a short version of the Technostress Scale. For this purpose, a sample of 1656 university students with an average age of 24.69 years (SD = 6.25; 78.25% female, 21 % male, 0.80% other) was analyzed. A short version of 10 items was obtained that met the expected validity, reliability, and acceptability. The items were clear, non-redundant and highly correlated with the total score of the scale to which they belonged (between .89 and .96). In addition, the second-order factor structure composed of ten items presented a good fit and good internal consistency. The correlations between the short and long versions of the scales were all positive and high (between .84 and .96). On the other hand, women scored significantly higher, and significant differences were found according to time spent using computers and cell phones for academic purposes. In addition, negative and significant associations were found between age and technostress. It is concluded from these analyses that the brief version of the Technostress Scale has adequate psychometric properties and may be useful both in academic research and in applied contexts. Both the scale and its corresponding scales are transferred.
Keywords: technostress; short version; university students